Sporotrichoid presentation of Mycobacterium marinum infection of the upper extremity - Belič, Mirjam (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2006)
Background: Mycobacterium marinum is a human opportunistic pathogen that is known to inhabit swimming pools, home aquariums, and natural bodies of salt and fresh water. Epidemic cases involving swimming pools are easily recognized, but sporadic cases are frequently misdiagnosed. Objective: A 42-year-old male presented with a 2-month history of the appearance of livid, verrucous, painless nodules on his upper extremity. He had cleaned an acquarium wiyh tropical fish for the past 2 years. Methods: A histopathological examination suggested a granulomatous inflammation. After incubation on Löwenstein-Jensen medium, Mycobacterium marinum was identified using biochemical methods and the PCR technique. Results: Systemic therapy with rifampicin, ethambutol, and clarithromycin over a period of 6 months led to complete resolution of the skin lesions with some residual scars. Conclusion: Knowledge of this condition is very important to avoid unnecessay diagnostic procedures and improper treatment.
Keywords: bakterijske infekcije; diagnosis; Diagnostika; kožne bolezni; Kožne bolezni, infekcijske; Mikobakterium marinum; Mycobacterium marinum; Skin Diseases, Infectious; therapy; Zdravljenje